Tom Regan's Philosophy of Animal Rights: Subjects-of-a-Life in the Context of Discussions of Intrinsic and Inherent Worth. - Lengauer, Erwin (Problems / Problemos, 2020)
Modern animal rights debates began in the 1970s, mainly as part of the budding field of applied ethics in Anglo-American philosophy. In just a short time, these animal rights discourses received international academic respect, especially through analytically trained philosophers. Central for this development was the analysis that rights language can be principally used species neutrally. This paper's contribution is to examine the central terms of Tom Regan's still widely discussed theory for their actuality and usefulness. Hence strengthening these arguments for modern animal rights theory as a serious approach in (inter)national ethical and legal disputes.